Research of the effect of miR-663 on the proliferation of prostate cancer cells, and the correlations of miR-663 with pathological grade and clinical stage - Wang, Shifeng; Liu, Jingsong; Li, Changming; Yang, Xue (Journal of B.U. ON., 2017)
To investigate the effect of miR-663 on the proliferation of prostate cancer (PCa) cells, and the correlations of miR-663 with pathological grade and clinical stage. PC-3 and DU-145 PCa cell lines were transfected by artificially synthesized miR-663 and its antisense plasmid, and cell proliferation was assessed using 5-ethynyl-2'-deoxyuridine and methyl thiazolyl tetrazolium assays. Real-time polymerase chain reaction (RT-PCR) was applied to assess the expression of miR-663 in tissue samples collected from 46 patients who were diagnosed with PCa but did not receive any treatment. Another 20 healthy subjects served as controls. According to morphologic and clinical data of tumor tissues in hematoxylin & eosin stained sections, we investigated the correlations of miR-663 with the pathological grade and clinical stage of PCa. miR-663 transfection significantly increased the proliferation of PC-3 and DU-145 cells, while transfection of the miR-663 antisense plasmid inhibited the proliferation of PC-3 and DU-145 cells. This suggested that miR-663 can promote the metastasis of PCa. Through detection of the tissue expression of miR-663, the highest and lowest expression of miR-663 were found in the PCa group and healthy group, respectively. Therefore, increased expression of miR-663 in PCa patients was associated with the grade of malignancy . The expression of miR-663 was positively correlated with pathological stage (p<0.05; r=0.7404), and with the clinical stage (p<0.05;r=0.8610), suggesting that miR-663 is closely correlated with the pathological grade and clinical stage of PCa. PDGFRα and PDGFRβ were frequently expressed on malignant PCs. We found that increased PDGFRβ expression was strongly associated with advanced disease and adverse prognosis. The expression of PDGFRα and MDV were not correlated with specific features. miR-663 can significantly increase the proliferation of PCa cells, and its expression is closely correlated with the pathological grade and clinical stage of PCa. Thus, miR-663 is expected to serve as a key predictor of disease stage progression.